Do ginger footbaths improve symptoms of insomnia more than footbaths with warm water only? - A randomized controlled study - Silja Kuderer; Katrin Vagedes; Henrik Szöke; Matthias Kohl; Stefanie Joos; Peter W. Gündling; Jan Vagedes (Elsevier, 2022)
Objectives: To compare the effects between warm water (WW) and ginger footbaths (WW+ginger) on sleep quality and warmth regulation in adults with self-reported insomnia symptoms. Methods: A prospective randomized-controlled study in which 28 participants (mean age 50.9 years, 64.3% women, insomnia symptom duration 11.4 years) were randomized to receive WW (n = 13) or WW+ginger (n = 15) daily for 2 weeks. Treatment involved nightly footbaths (12 liters of 38-42 °C warm tap water, maximum duration 20 min) with and without topical ginger (80 g of powdered ginger rhizomes). Main outcome measures: The primary outcome measure was self-reported sleep quality (global score from Pittsburgh Sleep Quality Index, PSQI) at 2 weeks. Secondary outcomes included measures of insomnia severity (Insomnia Severity Index, ISI) and warmth regulation (Herdecke Warmth Perception Questionnaire, HWPQ and 24-hour distal-proximal skin temperature gradient, DPG). Results: WW+ginger had no greater effect on PSQI (mean between-difference 0.0 [95% CI −3.0 to 2.9], Cohen's d=0.0) or ISI (−0.2 [−3.9 to 3.4], 0.0) than WW. Nor were there any significant differences in HWPQ perceived warmth (0.1 ≥d≥0.5) or DPG (0.1 ≥d≥0.4) between WW and WW+ginger. Both groups improved over time in PSQI (WW+ginger: d=0.7, WW: d=1.3) and ISI (WW+ginger: d=0.8, WW: d=1.0). Perceived warmth of the feet increased only in WW+ginger over time (d=0.6, WW: d=0.0). Conclusions: This dose of ginger (6.67 g/liter) did not have greater effects on sleep quality, insomnia severity or warmth regulation than WW. Considering effect sizes, costs and risks, the use of WW would be recommended over WW+ginger in this patient population.